Cytogenetic analysis on geographically distant parthenogenetic populations of Tityus trivittatus Kraepelin, 1898 (Scorpiones, Buthidae): karyotype, constitutive heterochromatin and rDNA localization - Adilardi, Renzo Sebastián (2014)
Tityus trivittatus Kraepelin, 1898 is the most medically important scorpion species of Argentina, and parthenogenetic populations are present in the major cities of this country. We performed a detailed cytogenetic analysis of specimens of three synanthropic parthenogenetic populations, all distant about 900 km from each other, using Ag-NOR, C-banding, DAPI/CMA3 staining and FISH with autologous 28S rDNA probes. The karyotype of females and embryos from the three populations showed 2n=6, with two large and four middle-sized holokinetic chromosomes. Constitutive heterochromatin was found in terminal and interstitial location and its pattern allowed the identification of three chromosome pairs. NORs were found on the terminal heterochromatic region of one pair of middle-sized chromosomes. The use of fluorochromes to characterize heterochromatin showed the absence of GC-rich heterochromatin and a low and variable number of AT-rich heterochromatic regions. We propose that a possible explanation for the lack of karyotypic variation between these geographically distant populations could be a recent colonization of urban areas by human means of synanthropic specimens from a single lineage of northeastern Argentina.